The Training Game that Teachers are Expected to Join in - Ramachandran, Vimala (Voices of Teachers and Teacher Educators, 2018)
This article explores the interlinkages between orientation of teachers after they are recruited, their working conditions and in-service teacher capacity building and how the three together influence the day to day practice of teachers in school. Bringing about change demands a multipronged strategy that addresses the needs and concerns of teachers from the ground up.